Knockdown of TTC9 inhibits the proliferation, migration and invasion, but induces the apoptosis of lung adenocarcinoma cells. Issue 11 (November 2022) - Huang, Xiaoyue; Jiang, Lingyu; Wen, Zhaoke; Yuan, Mingqing; Zhong, Yonglong
Abstract: Lung adenocarcinoma (LUAD) is one of the most commonly diagnosed subtypes of lung cancer, and one of the deadliest cancers. Tetratricopeptide repeat domain 9A (TTC9) is upregulated and has played an oncogenic role in some malignant tumors. However, the expression and role of TTC9 has not yet been elucidated in LUAD. Here, we investigated the expression profiles, biological functions and potential molecular mechanism of the TTC9 gene in LUAD. TTC9 expression was significantly overexpressed in LUAD tissues compared with that in normal lung tissues. TTC9 expression was closely correlated with gender, lymph node metastasis, and survival status in the TCGA-LUAD cohort. Subsequent cellular function assays demonstrated that knockdown of TTC9 promoted PC9 cell apoptosis and inhibited cell proliferation, migration and invasion, leading to cell cycle arrest in G2 phase. Moreover, inhibition of TTC9 suppressed the tumorigenicity of PC9 cells in nude mice. TTC9 might serve as oncogene in LUAD through cancer-related signaling pathways including p38 MAPK pathway. The expression of TTC9 gene might be modulated by DNA copy number variant and DNA methylation. TTC9 was significantly associated with tumor immune infiltration patterns. Accordingly, TTC9 may be a novel therapeutic target for the treatment of LUAD. Abstract : TTC9; LUAD; Bioinformatics analysis; p38 MAPK; Proliferation; Flow cytometry.